FTIR spectroscopy of methyl butanoate-air and propane-air low pressure flat flames - Naber, Kristen Ann, author; Marchese, Anthony, advisor; Catton, Kimberly, committee member; Gao, Xinfeng, committee member (Colorado State University. Libraries, 2012)
The combustion of fatty acid methyl esters (FAME) in diesel engines has been shown to produce lower emissions of carbon monoxide (CO), unburned hydrocarbons, greenhouse carbon dioxide (CO2), and particulate matter than petroleum based fuels. However, most diesel engine studies have shown that emission of oxides of nitrogen (NOx) typically increase for methyl ester fuels in comparison to petroleum based fuels. Many theories have been proposed to explain these NOx increases from FAME combustion but a general consensus has emerged toward two primary mechanisms: (1) the increased bulk modulus of biodiesel results in earlier fuel injection into the cylinder and/or (2) the presence of oxygen in the fuel results in a leaner (but still rich) premixed autoignition zone thereby increasing the local flame temperature during the premixed burn phase. It is well known that NOx is produced during the combustion of hydrocarbons in air from three different mechanisms: prompt NOx, thermal NOx, and via fuel bound nitrogen. Both of the mechanisms that have been proposed to explain the observed NOx increases from the combustion of FAME in diesel engines are related to the thermal NOx production route. However, no quantitative data exist on local in-cylinder temperatures and associated in-cylinder NO production during the premixed autoignition phase to experimentally verify these hypotheses. The present work is aimed at developing an experimental approach to examine a third hypothesis that suggests that the chemical structure of methyl esters results in an increase in prompt NOx in comparison to non-oxygenated hydrocarbons. This new hypothesis has the potential to be verified by conducting experiments with steady, laminar flames. Accordingly, in the present study, low pressure, flat flame burner experiments were conducted, which enabled direct temperature measurements using a thermocouple and direct species sampling using a quartz microprobe. The fuels used in the flame experiments were propane (C3H8) and methyl butanoate (C5H10O2), a small methyl ester fuel whose chemical kinetic mechanism has been the subject of substantial research in the past decade. The gas samples were directed to an FTIR spectrometer for analysis of various species including NO, CO, and CO2. Equivalence ratios of φ = 0.8, 1.0, and 1.2 were examined for both fuels. Temperatures were obtained using coated Pt-Pt/13%Rh type R thermocouples and were corrected for radiation losses. In addition to the experiments, laminar flame modeling studies were conducted using CHEMKIN for the both fuel types at each equivalence ratio using existing detailed chemical kinetic mechanisms to predict temperature and species concentrations. Because no methyl butanoate mechanisms containing detailed NOx chemistry exist, the propane/NOx chemical kinetic mechanism of Konnov and was combined with a detailed methyl butanoate mechanism Gail and coworkers. Experimental and modeling results show that nitric oxide production in the steady, premixed laminar methyl butanoate flames did not differ substantially from that produced in similar propane flames. Results were inconclusive on which nitric oxide formation mechanisms contributed to the overall measured concentrations.
Keywords: combustion; FAME; flat flame; FTIR; low pressure; methyl butanoate